A HOLISTIC ANALYSIS ON THE EFFECT OF CRITICAL THINKING PRACTICES IN EDUCATION ON ATTITUDE: MIXED-META ANALYSIS - Evcimik, Sare; Örenç, Elif (International Online Journal of Education and Teaching, 2024)
<p class="Saptanm" style="text-align: justify; line-height: 115%; tab-stops: 28.0pt 56.0pt 84.0pt 112.0pt 140.0pt 168.0pt 196.0pt 224.0pt 252.0pt 280.0pt 308.0pt 336.0pt 364.0pt 392.0pt 420.0pt 448.0pt 476.0pt; margin: 0cm 0cm 8.0pt 0cm;">The aim of this study is to analyze the effectiveness of applied research on the effect of critical thinking skills, which is very important in the epistemology of the Information Age, on student attitudes. The study was conducted with a mixed-meta method, based on document analysis and consisting of meta-analysis (quantitative) and meta-thematic (qualitative) dimensions. In this context, studies on the effect of critical thinking on student attitudes covering the years 2003-2021 were scanned in Turkish and English sources. Depending on the inclusion criteria in accordance with the relevant methodology, five studies were analyzed with the CMA data analysis program and the effect size of critical thinking on attitude was calculated as g = 0.738 at a "medium level". Accordingly, it can be said that critical thinking skills have a positive effect on students’ attitudes towards the course. Within the scope of the meta-thematic analysis process, 12 studies were reached within certain criteria. These studies were examined with the content analysis method and certain themes and codes were reached. As a result, the themes of "the impact of critical thinking practices on individual development", "the impact on 21st century skills" and "the impact on the learning process" were obtained. By consulting an expert opinion, it was confirmed that these themes and codes were compatible. As a result of the study, it was determined that the results of the meta thematic analysis supported the results of the meta analysis. In the study, this situation was evaluated as critical thinking practices not only have positive effects on students’ attitudes, but also support students’ academic development in cognitive terms. <p class="Saptanm" style="text-align: justify; line-height: 115%; tab-stops: 28.0pt 56.0pt 84.0pt 112.0pt 140.0pt 168.0pt 196.0pt 224.0pt 252.0pt 280.0pt 308.0pt 336.0pt 364.0pt 392.0pt 420.0pt 448.0pt 476.0pt; margin: 0cm 0cm 8.0pt 0cm;">Keywords: Critical thinking, Attitude, Meta-analysis, Meta-thematics.